The complexity of malignant glioma treatment - Kampers, Linde F. C.; Metselaar, Dennis S.; Vinci, Maria; Scirocchi, Fabio; Veldhuijzen van Zanten, Sophie; Eyrich, Matthias; Biassoni, Veronica; Hulleman, Esther; Karremann, Michael; Stücker, Wilfried; Van Gool, Stefaan W. (Cancers, 2025)
Malignant glioma is a highly aggressive, therapeutically non-responsive, and deadly disease with a unique tumor microenvironment (TME). Of the 14 currently recognized and described cancer hallmarks, five are especially implicated in malignant glioma and targetable with repurposed drugs: cancer stem-like cells, in general, and glioma stem-like cells in particular (GSCs), vascularization and hypoxia, metabolic reprogramming, tumor-promoting inflammation and sustained proliferative signaling. Each hallmark drives malignant glioma development, both individually and through interactions with other hallmarks, in which the TME plays a critical role. To combat the aggressive malignant glioma spatio-temporal heterogeneity driven by TME interactions, and to overcome its therapeutic challenges, a combined treatment strategy including anticancer therapies, repurposed drugs and multimodal immunotherapy should be the aim for future treatment approaches.
Gesehen am 31.07.2025